2010
DOI: 10.1111/j.1574-6941.2009.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase genes revealed and compared in bacterial isolates, DNA extracts and a metagenomic library from a phytopathogen-suppressive soil

Abstract: Soil that is suppressive to disease caused by fungal pathogens is an interesting source to target for novel chitinases that might be contributing towards disease suppression. In this study, we screened for chitinase genes, in a phytopathogen-suppressive soil in three ways: (1) from a metagenomic library constructed from microbial cells extracted from soil, (2) from directly extracted DNA and (3) from bacterial isolates with antifungal and chitinase activities. Terminal restriction fragment length polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 47 publications
1
63
0
3
Order By: Relevance
“…From previous work based on isolated microbial community members, it has been postulated that the addition of chitin to soil stimulates bacterial communities more than fungal ones (8,9). Among the bacterial isolates obtained in several studies, members of the genus Streptomyces were dominant (10), followed by Stenotrophomonas and Bacillus (1,11,12). The presence of these bacterial chitinolytic groups was confirmed by analyses based on the 16S rRNA and chitinase (chiA) genes (11,13).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…From previous work based on isolated microbial community members, it has been postulated that the addition of chitin to soil stimulates bacterial communities more than fungal ones (8,9). Among the bacterial isolates obtained in several studies, members of the genus Streptomyces were dominant (10), followed by Stenotrophomonas and Bacillus (1,11,12). The presence of these bacterial chitinolytic groups was confirmed by analyses based on the 16S rRNA and chitinase (chiA) genes (11,13).…”
mentioning
confidence: 80%
“…Among the bacterial isolates obtained in several studies, members of the genus Streptomyces were dominant (10), followed by Stenotrophomonas and Bacillus (1,11,12). The presence of these bacterial chitinolytic groups was confirmed by analyses based on the 16S rRNA and chitinase (chiA) genes (11,13). Experiments performed in plots of natural fields, in which chitin was placed in litter bags, have addressed and revealed the molecular diversity of the chitinases produced by Streptomyces (14).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This should help to reveal the huge potential of suppressive soils for managing soilborne pathogens. Characterization of the potential may be "easy" when biological nature of the suppression is known as illustrated by studies of soils with known chitinase and antifungal activities (Hjort et al, 2010). Metagenomics may also lead to screen uncultured microorganisms from soil which represent a potentially rich source of useful natural products.…”
Section: The Interactions Of the Pathogen Within A Microbial Communitymentioning
confidence: 99%
“…Yet, the results to date are falling short of expectations. For instance, it remains unclear what percentage of the DNA present in soils is extracted by current techniques, and how representative this fraction is (Thakuria et al, 2008;Hjort et al, 2010;Trevors, 2009). This is clearly illustrated in a study by Ascher et al (2009), who applied a novel DNA extraction protocol to two forest soils and observed that sequential extraction leads to increased DNA recovery, that extracellular DNA can represent a very sizeable (34.6%) portion of the sum of extracellular and intracellular DNA, and that a very different perception of microbial diversity emerges if one considers the total extracted DNA or just the extracted intracellular DNA.…”
Section: Soil Biodiversitymentioning
confidence: 99%